Control of the power quality for a DFIG powered by multilevel inverters - H. Hachemi; A. Allali; B. Belkacem (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper treats the modeling, and the control of a wind power system based on a doubly fed induction generator DFIG, the stator is directly connected to the grid, while the rotor is powered by multilevel inverters. In order to get a decoupled system of controlfor an independently transits of active and reactive power, a vector control method based on stator flux orientation SFOC is considered: Direct vector control based on PI controllers. Cascaded H-bridge CHBI multilevel inverters are used in the rotor circuit to study its effect on supply power quality. All simulation models are built in MATLAB/Simulink software. Results and waveforms clearly show the effectiveness of vector control strategy. Finally, performances of the system will tested and compared for each levels of inverter.